Chimney Technique with Nellix EndoVascular Aneurysm Sealing System in a Patient with Single Kidney and Juxtarenal Abdominal Aortic Aneurysm - Kisis, Kaspars; Savlovskis, Janis; Gedins, Marcis; Ezite, Natalija; Zellans, Edgars; Krievins, Dainis (AORTA, 2016)
We present a saccular asymptomatic juxtarenal abdominal aortic aneurysm in a 70-year-old male with a very short left renal artery supplying the only kidney. The case was successfully treated with the Nellix EndoVascular Aneurysm Sealing system combined with a chimney technique.
Keywords: Abdominal aortic aneurysm; Endovascular aortic aneurysm repair; Chimney technique; Single kidney; EVAS